1984
DOI: 10.3382/ps.0630730
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Phosphorus in Commercial Phosphate Supplements for Turkeys

Abstract: Forty-seven commercial phosphorus supplements were obtained from feed manufacturers and subjected to biological phosphorus availability assay using the turkey poult. Bone ash was the response criterion. Compared to a reference source of commercial mono/ dicalcium phosphate (assigned 100), 7 other mono/ dicalcium phosphates averaged 97.1 (range 88.6 to 110.0), 20 dicalcium phosphate sources averaged 90.6 (76.3 to 104.8), and 20 defluorinated phosphate sources averaged 78.4% (68.6 to 89.6) availabilities. Combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 6 publications
3
16
1
1
Order By: Relevance
“…Commercial defluorinated phosphates were only 86% as biologically effective as the dicalcium phosphates. Waibel et al (1984) reported similar results. With the biological value of 7 monocalcium and dicalcium phosphates (21% P) set at 100%, they reported that the average biological values of 20 dicalcium phosphates (18.5%) and of 20 defluorinated phosphates were 93 and 81%, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Commercial defluorinated phosphates were only 86% as biologically effective as the dicalcium phosphates. Waibel et al (1984) reported similar results. With the biological value of 7 monocalcium and dicalcium phosphates (21% P) set at 100%, they reported that the average biological values of 20 dicalcium phosphates (18.5%) and of 20 defluorinated phosphates were 93 and 81%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Other researchers have also used this compound as a standard (Wilcox et al, 1955;Hurwitz, 1964) or have used reagent grade monocalcium phosphate monohydrate (Motzok et al 1956;Waibel et al 1984). These hydrated compounds are highly utilized and provide a better standard for attainment than 3-tricalcium phosphate.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other experimental details were as those reported by Waibel et al (1983). The basal assay diet was a corn-soybean meal diet containing .44% total phosphorus and 1.24% calcium.…”
Section: Methodsmentioning
confidence: 99%